1997
DOI: 10.1214/aos/1031833663
|View full text |Cite
|
Sign up to set email alerts
|

On the efficiency of multivariate spatial sign and rank tests

Abstract: Asymptotic Pitman efficiencies of multivariate spatial sign and rank methods are considered in the one-sample location case. Limiting distributions of the spatial sign and signed-rank tests under the null hypothesis as well as under contiguous sequences of alternatives are given. Formulae for asymptotic relative efficiencies are found and, under multivariate t distributions, relative efficiencies with respect to Hotelling's T 2 test are calculated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 17 publications
2
51
0
Order By: Relevance
“…A study of the sign-based and rank-based MANOVA tests showed that they are comparable to the Hotelling T 2 test for normally distributed data but have significantly more power than the Hotelling T 2 for non-normally distributed data. 11 Our reanalysis of the data of Gross and Miller 5 showed that the data in the 2 treatment groups did not follow a multivariate normal distribution at all Figure 2. Double-angle plots of vector astigmatism outcomes between 2 groups for test data sets 1 through 6.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A study of the sign-based and rank-based MANOVA tests showed that they are comparable to the Hotelling T 2 test for normally distributed data but have significantly more power than the Hotelling T 2 for non-normally distributed data. 11 Our reanalysis of the data of Gross and Miller 5 showed that the data in the 2 treatment groups did not follow a multivariate normal distribution at all Figure 2. Double-angle plots of vector astigmatism outcomes between 2 groups for test data sets 1 through 6.…”
Section: Discussionmentioning
confidence: 78%
“…These strategies do not depend on the distribution of data and are valid under very mild assumptions. [8][9][10] A study of the efficiencies of the sign-based and rank-based methods 11 showed that they are better than traditional parametric methods when the data are not normally distributed.…”
mentioning
confidence: 99%
“…In this case, Mottonen and Oja (995) stated that the median test has the same efficiency as their spatial two-sample sign test as well as the two-sample sign test of Randles and Peters (990) (see also Mottonen et al 1997). We use the …”
Section: The Test Statisticsmentioning
confidence: 99%
“…Mottonen and Oja (1995) have provided an excellent overview of these methods. (Other literature on the subject includes Blumen 1958; Brown and Hettmansperger 1987Hettmansperger , 1989Chaudhuri and Sengupta 1993;Dietz 1982;Hettmansperger, Nyblom, and Oja 1994;Hodges 1955;Hossjer and Croux 1995;Mardia 1967;Tienari 1997;Oja and Nyblom 1989, 1991, Randles 1989 Among the tests that we study, the Hotelling and median have the advantage of being affine invariant. The coordinate test is invariant under coordinatewise monotone transformations, and the direction test is rotationally invariant.…”
mentioning
confidence: 99%
“…However, the nonparametric estimation of multivariate location is more efficiently done-even when the interest lies in the univariate marginals-by multivariate techniques. In the bivariate normal case, for example, the asymptotic efficiency of the spatial median relative to the sample mean is 0.785, while the vector of the marginal medians inherits the efficiency of 0.637 from the univariate case (Brown 1983;Möttönen et al 1997). For heavy tailed distributions, the spatial median is more efficient than the mean.…”
Section: Introductionmentioning
confidence: 99%